2019
DOI: 10.1038/s41389-019-0125-3
|View full text |Cite
|
Sign up to set email alerts
|

An FBXW7-ZEB2 axis links EMT and tumour microenvironment to promote colorectal cancer stem cells and chemoresistance

Abstract: Colorectal cancer (CRC) patients develop recurrence after chemotherapy owing to the survival of stem cell-like cells referred to as cancer stem-like cells (CSCs). The origin of CSCs is linked to the epithelial–mesenchymal transition (EMT) process. Currently, it remains poorly understood how EMT programmes enable CSCs residing in the tumour microenvironment to escape the effects of chemotherapy. This study identifies a key molecular pathway that is responsible for the formation of drug-resistant CSC populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(109 citation statements)
references
References 58 publications
3
106
0
Order By: Relevance
“…In CRC, the FBXW7-ZEB2 axis has been demonstrated to control a number of important EMT associated characteristics as well as drug resistance. ZEB2 knockdown was able to reverse the EMT phenotype induced by loss of FBXW7, a tumour suppressor [81] . Similarly, overexpression [70] or upregulation [71,73] of TWIST has resulted in chemoresistance in cancer cells; mechanistically, in bladder cancer, this has been shown to be through the upregulation of P-Glycoprotein [72] .…”
Section: Drug Resistance: Where Does Emt Come Into Play?mentioning
confidence: 96%
See 1 more Smart Citation
“…In CRC, the FBXW7-ZEB2 axis has been demonstrated to control a number of important EMT associated characteristics as well as drug resistance. ZEB2 knockdown was able to reverse the EMT phenotype induced by loss of FBXW7, a tumour suppressor [81] . Similarly, overexpression [70] or upregulation [71,73] of TWIST has resulted in chemoresistance in cancer cells; mechanistically, in bladder cancer, this has been shown to be through the upregulation of P-Glycoprotein [72] .…”
Section: Drug Resistance: Where Does Emt Come Into Play?mentioning
confidence: 96%
“…Numerous studies in a variety of tissue types have also found EMT-TFs, namely SNAIL1/2, ZEB1/2 and TWIST, to directly confer drug-resistance in cancer [70][71][72][73][74][75][76][77][78][79][80][81] , as summarised in Table 2. Upregulation of these transcription factors alone can be sufficient to confer drug resistance [71,75] .…”
Section: Drug Resistance: Where Does Emt Come Into Play?mentioning
confidence: 99%
“…options and therapeutic outcome. EMT is linked not only to increased metastasis (Yang et al, 2004;Mani et al, 2007;Ocana et al, 2012;Stankic et al, 2013) but also to chemoresistance (Singh and Settleman, 2010;Haslehurst et al, 2012;Ren et al, 2013;Fischer et al, 2015;Zheng et al, 2015;Li H. et al, 2019;Li N. et al, 2019). EMT in cancer is associated with the acquisition of a more stem-cell-like character.…”
Section: The Ecm Regulates Emt and Metastasismentioning
confidence: 99%
“…Among these, ZEB2 has been shown to regulate epithelial cell plasticity and proliferation, but also to balance stemness and differentiation, standing as a master regulator of cell state transitions [24][25][26]. Notably, ZEB2 was also recently recognized as a factor implicated in drug resistance in CRC through FBXW7 E3-ubiquitin ligase binding [27]. Moreover, ZEB2 expression was associated with poor oncologic outcome and distant recurrence, emerging as a new clinical biomarker in CRC [28].…”
mentioning
confidence: 99%